A values-based quality management model for Madrasahs: Evidence from the Tri Harakah program - Athok Fu'adi; Fuad Anwar (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2026)
Improving the quality of madrasah education requires management approaches that integrate academic excellence with Islamic values and community engagement. Although numerous initiatives have been introduced to strengthen governance and quality assurance, limited research has examined how values-based institutional programs function as comprehensive quality management systems. This study investigates the implementation of the Tri Harakah Program as a quality management model in madrasahs in Karangjati Subdistrict, Ngawi Regency, Indonesia. Employing a qualitative case study design, the research involved 32 participants, including principals, teachers, students, committee members, and community representatives selected through purposive sampling. Data were collected through semi-structured interviews, participant observations, and document analysis, and analyzed using the Miles, Huberman, and Saldaña interactive model. The findings reveal that the Tri Harakah Program strengthens institutional quality through three complementary dimensions: the Madrasah Awards enhance teacher accountability and administrative discipline; the Tahfidz Program cultivates students’ spiritual discipline and learning routines; and the integration of local wisdom reinforces character education and community participation. Leadership commitment, institutional support, and dedicated funding emerged as key enabling factors, whereas administrative workload and limited Tahfidz teachers constrained implementation. The study proposes Tri Harakah as a values-based quality management model that integrates academic, spiritual, and sociocultural dimensions, offering practical guidance for strengthening governance, quality assurance, and sustainable institutional improvement in Islamic education.